The determine factors of student satisfaction with e-learning in Malaysia Higher Education Institutions: a scoping review. Issue 1 (May 2021) - Mohamed, B; Noorashid, N A; Abd Razak, F Z
Abstract: The aim of this scoping review is to investigate work published on student satisfaction with e-learning in Malaysia Higher Learning Institutions (HLIs). A scoping review was conducted using the methodological framework of Arksey and O'Malley to identify a broad range of relevant literature, regardless of study design. A systematic search was performed using Google Scholar in May 2020 and then was updated in October 2020. The database was searched for literature published between 1 st January 2019 and October 2020. Two authors independently assessed literature eligibility and extracted data to answer our research question 'From the previous literature, what is the effects of e-learning/LMS on student learning satisfaction in Malaysia Higher Learning Institutions?' Seven articles were included in the review. There appears to be a paucity of research regarding student satisfaction with e-learning in Malaysia HLIs. Various theories and models have been included in the papers. However, all the articles mentioned the factors that determine student satisfaction with e-learning. The study demonstrates that when e-learning is delivered purposefully and effectively in the management and support of student learning, it has a positive effect on student satisfaction. However, more research in this area is required.